Analysis of the Influence of Customer Relationship Management on Customer Loyalty of Indomaret Palembang City - Ali Ibrahim; Dytha Ananda Widhiarso; Umi Pertiwi; Wiwit Widhya; Satria Alva Ardana; Rafif Nopyefa (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
One of the requirements to be a successful business is to have loyal or loyal customers. Customer Relationship Management is one of the most widely used methods in the business world to manage data and customer relationships so that customers will remain loyal to the products or services offered. Indomaret Palembang City itself has used CRM in its daily business activities. Currently, Indomaret already has many business rivals who give the same or better offers than them. Therefore, Indomaret Palembang city needs the right strategy to get customers who have high loyalty. This research was conducted to analyze the presence or absence of and how much influence the implementation of Customer Relationship Management has on the level of Customer Loyalty of Indomaret Palembang City. This research was conducted using a quantitative approach method. Data collection for this research was done by distributing questionnaires. Respondents in this study amounted to 100 respondents. The results of the analysis and research that have been carried out show that there is a significant influence between the application of CRM on customer loyalty at Indomaret Palembang. This can be seen from the results of the T-Test (Partial) and the Linear Regression Analysis that has been carried out which shows the value of a significant influence between the CRM variables and customer loyalty. Therefore, from this study, it was found that the application of Customer Relationship Management can have a significant effect on customer loyalty at Indomaret Palembang.